Bezugla L. R. Propositional markers of implicit meaning in the German dialogical discourse - Bezugla L. R. (Philological Treatises, 2020)
The article deals with the propositional markers of implicit meaning – verbal means, indicating the presence in the utterance of an implicit propositional meaning. As such markers in the German dialogical discourse function lexical means, expressing propositional elements – argument, predicate, connector, modificator, presupposition, or the whole proposition, and syntactic means – parcelling, contraposition, addition, unreal conditional and hypothetic comparative sentence.